Role Conflict, Self Efficacy, Employees Performance and Organizational Performance - Fahmi, Hadi Kurnia; Musnadi, Said; Nadirsyah, Nadirsyah (Universitas Syiah Kuala, 2019)
AbstractObjective This study aims to analyze the influence of role conflict and self-efficacy towards employees performance and its implications on organizational performance at Inspectorate of Nagan Raya District, Aceh, Indonesia.Design/methodology The sample of this study is 120 auditors. The data was collected through questionnaire and analyzed using Structural Equation Model (SEM).Results The study found that role conflict and self-efficacy have positive and significant influence on employees performance and inspectorate performance at Nagan Raya District. Meanwhile employees performance mediates the effect of role conflict and self-efficacy towards inspectorate performance at Nagan Raya District.